1993
DOI: 10.1021/ic00066a032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of lanthanide(III) texaphyrins

Abstract: decaene (30), respectively, are reported. Single crystals suitable for X-ray diffraction were obtained for the La(III) complex 3, the Gd(III) complexes 9 and 37, the Eu(III) complex 36, and the Lu(III) complex 22, by dissolving the respective complex in MeOH/CHC^a nd layering with diethyl ether. The five lanthanide(lll) texaphyrin complexes all crystallize in the triclinic space group, P\ (No. 2), with Z = 2. The final R's, for data collected at reduced temperatures (<-90 °C), were 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
133
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 0 publications
6
133
0
1
Order By: Relevance
“…This instability stands in contrast to what is true for most meso-free sp 3 -texaphyrins, which are generally quite stable and which can be separated by column chromatography over various supports with nearly quantitative recovery. 18,19 A possible explanation for the instability of 8 is that the two meso-aryl groups introduce strain that make the imine bonds more susceptible to solvolysis. While not an exact analogy, it is noteworthy that several meso-aryl substituted porphyrins have been reported that have distorted non-planar conformations.…”
Section: Synthesismentioning
confidence: 99%
“…This instability stands in contrast to what is true for most meso-free sp 3 -texaphyrins, which are generally quite stable and which can be separated by column chromatography over various supports with nearly quantitative recovery. 18,19 A possible explanation for the instability of 8 is that the two meso-aryl groups introduce strain that make the imine bonds more susceptible to solvolysis. While not an exact analogy, it is noteworthy that several meso-aryl substituted porphyrins have been reported that have distorted non-planar conformations.…”
Section: Synthesismentioning
confidence: 99%
“…[16] Over the last few years, however, a small number of very promising q = 2 gadolinium complexes have been reported. [17][18][19] The introduction of three additional carboxylate groups on the heptadentate do3a 3À ligand suppresses anionic binding to the gadolinium centre by electrostatic repulsion.…”
mentioning
confidence: 99%
“…Monitoring the selective accumulation of gadolinium(III) texaphyrin in neoplasms by MRI enables the possibility of treatment planning and subsequent monitoring of the response I 2 of cancers to the radiation therapy. Gadolinium(III) texaphyrin is representative of a new class of compounds known as the texaphyrins (e.g., structures 1 and 2) (25)(26)(27).…”
mentioning
confidence: 99%
“…Texaphyrins are large planar porphyrin-like macrocycles that are capable of coordinating a range of relatively large cations, including Gd(III) and other members of the trivalent lanthanide series (26,27). In general, the complexes formed are stable and of a 1:1 metal-to-ligand stoichiometry (27 25 ,us after the pulse.…”
mentioning
confidence: 99%